Meta-analisis Persepsi Peserta Didik Peminatan IPA Terhadap Pembelajaran Biologi - Nataniel Marco Antonio Gultom; Rahmadhani Fitri (Departement of Mathematics Education, 2024)
Perception is a process involving sensing and interpreting data from the environment, which plays an important role in the interaction between individuals and their social contexts. This study aims to identify students' perceptions of biology learning, which is often considered difficult due to the complexity of scientific concepts and terminology. Using a meta-analysis method, this study analyzed ten articles from national journals regarding students' perceptions in biology learning. The results of the analysis showed that students' perceptions were generally positive, but there were still challenges in understanding some materials. Several factors such as teaching style, learning methods, and the relevance of the material to everyday life influenced these perceptions. This study also highlighted the importance of practicum-based learning and the use of digital media, such as Google Classroom, in improving understanding and motivation to learn. The conclusion shows that by increasing positive perceptions and strengthening conceptual understanding, biology learning outcomes can be significantly improved